Strategi Dakwah Sunan Ampel dalam Konteks Multikultural - Ikhwanul Habib; Fatma Dewi Adjiji; Vivia Salma Azzaahro; Miftahul Huda (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2025)
The spread of Islam in Indonesia began in the mid-7th century AD. This process is inseparable from the role of Walisongo, a group of scholars and Sufism experts who played an important role, especially in Java. One of the figures who contributed greatly to the spread of Islam in East Java was Sunan Ampel. The purpose of this study is to find out about Sunan Ampel's da'wah strategy in the context of Multicultural in Java and its approach and implementation. This research uses library research method. The main sources used in carrying out this research are relevant sources, both primary books, journals, documents or other records. The results and discussion of this research concluded that Sunan Ampel's da'wah strategy in a multicultural context through cultural traditions in the local community, interfaith dialog, and religious education was considered very influential in preaching Islam in Indonesia, especially in Java. Through the da'wah strategy applied by Sunan Ampel, it has relevance to the modern era by adopting da'wah teachings with local culture, inclusive methods, and producing a community with character